Factor structure, internal consistency and distribution of Female Sexual Function Index among Mexican women with early diagnostic of breast cancer - Miaja Avila, Melina; Moral de la Rubia, José; Fonseca, Alan; Cruz Ramos, Marlid; Villarreal Garza, Cynthia; Becerril Gaitán, Andrea; Vaca Cartagena, Bryan Francisco; Ferrigno Guajardo, Ana Sofía (Psicooncología, 2021)
Background: Female Sexual Dysfunction (FSD) occurs frequently in women with breast cancer due to oncologic treatments. It is essential to have a validated instrument to diagnose and quantify FSD in this population accurately. Objective: To validate the Female Sexual Function Index (FSFI). Method: The FSFI was applied to 272 sexually active Mexican women with recent diagnosis of breast cancer who had not initiated systemic cancer treatment. Results: The FSFI six-factor model is valid by confirmatory factor analysis, and the inventory and its factors have adequate internal consistency reliability. Conclusions: This study provides enough evidence about the reliability and factor structure of the FSFI questionnaire in the context of breast cancer clinical practice in Mexico.